Independent and Collaborative Contributions of the Cerebral Hemispheres to Emotional Processing - Shobe, Elizabeth R. (Frontiers in Human Neuroscience, 2014)
Presented is a model suggesting that the RH directly mediates the identification and comprehension of positive and negative emotional stimuli, whereas the LH contributes to higher level processing of emotional information that has been shared via the corpus callosum. RH subcortical connections provide initial processing of emotional stimuli, and their innervation to cortical structures provides a secondary pathway by which the hemispheres process emotional information more fully. It is suggested that the LH contribution to emotion processing is in emotional regulation, social well-being and adaptation, and transforming the RH emotional experience into propositional and verbal codes. Lastly, it is proposed that the LH has little ability at the level of emotion identification, having a default positive bias and no ability to identify a stimulus as negative. Instead, the LH must rely on the transfer of emotional information from the RH to engage higher order emotional processing. As such, either hemisphere can identify positive emotions, but they must collaborate for complete processing of negative emotions. Evidence presented draws from behavioral, neurological, and clinical research, including discussions of subcortical and cortical pathways, callosal agenesis, commissurototomy, emotion regulation, mood disorders, interpersonal interaction, language, and handedness. Directions for future research are offered.